Unusual Localization of Clostridium Difficile Infection in an Isolated Segment of the Descending Colon in a Critical Care Patient - Evgeni Brotfain; Leonid Koyfman; Amit Frenkel; Jochanan G. Peiser; Abraham Borer; Benjamin F. Gruenbaum; Alexander Zlotnik; Moti Klein (Case Reports in Surgery)
Unrecognized severe pseudomembranous colitis may become life threatening. A typical Clostridium difficile infection is associated with involvement of the colon; however, small bowel disease has also been described. Here, we present a case of a 48-year-old man with Clostridium difficile colitis of an isolated segment in the descending colon treated by a novel catheter intraluminal antibiotic irrigation. The intraluminal antibiotic irrigation was performed through a Foley catheter inserted into the isolated mucus fistula. The patient recovered after three weeks of intraluminal vancomycin (250 mg diluted in 150 ml of normal saline  x Q6) and metronidazole (500 mg  x Q8). Both antibiotics were given into the mucus fistula over 30 min. The patient was discharged from the unit four weeks after admission. This novel technique, in which the antibiotic was administered through an inserted intraluminal Foley urinary catheter, may be an efficient and safe alternative when conventional routes cannot be implemented.